ANALYSIS OF THE EFFECTIVENESS OF ONLINE ADVERTISING ON THE LEVEL OF BRAND AWARENESS AT PT TOKOPEDIA INDONESIA (Case Study on PT Tokopedia Users at DKJ Jakarta) - Didik Kurniawan; Zanuar Rizqi (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
Indonesia has experienced rapid growth in the e-commerce sector in recent years, there have been significant changes in increasing internet penetration, the growth of the middle class, and changes in consumer behavior that increasingly rely on online transactions. This study aims to determine the effect of the effectiveness of online advertising on the level of brand awareness at PT Tokopedia Indonesia for users in DKJ Jakarta. The method used in this research is quantitative method with a sample of 100 Tokopedia users using non-probability sampling technique. This study uses a google form in the form of a questionnaire distributed via social media, researchers apply a cross-sectional design to observe and analyze data from a population or sample at a certain point in time used, namely The result of the research is that online advertising is very effective in increasing Tokopedia brand awareness. The more often someone sees Tokopedia advertisements, the more likely they are to remember the brand. Demographic characteristics affect the level of brand awareness. Young users, women, and those with higher education tend to be more familiar with the Tokopedia brand. Repetition of advertising messages (frequency of viewing) is very important. The more often someone sees an ad, the stronger their memory of the brand.